The Lumpy Skin Disease Emergence and Management: A Case Study from the North Indian District of Rewari, Haryana - Nitin Yadav; Sneha Anand; Priya; Ujjwal; Rohan Yadav; Rajesh Yadav; Vinita Yadav (The Indian Veterinary Journal, 2024)
Lumpy skin disease (LSD) is an emerging viral illness in cattle that causes severe morbidity.Although the illness is not linked with substantial mortality; it causes significant economic losses owing to decreased feeding, abortion, decreased milk production, weight conversionand infertility, as well as damaged cattle skins.